Bikol magis through childhood days and youthful years - Castilla, Greg S.; Borjal, Raul F. (Naga City Ateneo de Naga University Press, 2014)
Collection of essays from students as Ateneo de Naga celebrates 75 years.
Tac-2508g donated by Prof. Pierce Docena on 09 Feb 2017.
Keywords: Ateneo de Naga University -- History; Philippine essays (English).